MODEL INFLUENCE PjBL BASED ON STEAM AND ENVIRONMENTAL CARE ATTITUDE TOWARDS COGNITIVE RETENTION OF STUDENTS OF GRADE IV SCIENCE SUBJECT AT SDN RAGUNAN 08: Jurnal Kajian Pendidikan Sains - Oktavia Widyawati; Irdalisa Irdalisa; Tri Isti Hartini (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
Research on project based learning includes Project Based Learning (PjBL), is a learning model that involves student in designing or creating projects that are innovative, useful in solving problems in daily life, and emphasizing contextual assessment learning. This study aims to find out whether or not there is an influence of the STEAM-based PjBL model and environmental care attitudes on students' cognitive retention in elementary school grade IV science learning. The learning model used in this study is an experimental method using a 2 x 2 factorial design design. The population of this study was 62 people, consisting of 31 students who learned using the STEAM-based PjBL model and 31 students who learned using the PjBL learning model. The research instrument was in the form of a questionnaire and multiple-choice test. The first hypothesis test using the Two-Path Anava Test was obtained with a sig value of Fcalculated > Ftable or 19.94 > 4.105, then Ho was rejected and H1 was accepted, meaning that there was an influence of the STEAM-based PjBL learning model on the cognitive retention of grade IV students of SDN Ragunan 08. The second hypothesis test using the Two-Path Anava Test obtained a value of Sig. Ftables, the value of Fcalculated > Ftable or 33.49 > 4.105, then Ho was accepted and H1 was rejected, meaning that there was no influence of environmental care on the cognitive retention ability of grade IV students of SDN Ragunan 08. The third hypothesis test using the Two-Path Anava Test obtained a value of Sig. Fcalculate < Ftable or 3.64 < 4.105, then Ho rejected and H1 accepted, meaning that there was no interaction between the STEAM-based PjBL learning model and the attitude of environmental care towards the cognitive retention ability of grade IV students at SDN Ragunan 08.